2021
DOI: 10.3390/ijerph18116039
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Curricular Assessment of Knowledge and Awareness of Intimate Partner Violence among First-Year Dental Students

Abstract: Background: Intimate partner violence (IPV) has previously been recognized as a major public health issue. Oral healthcare providers, such as dentists, are crucial to the screening and identifying of individuals experiencing IPV, since most injuries occur in the head and neck region. A lack of knowledge and awareness regarding teaching and learning about IPV in dental school curricula has been identified. Based upon the overall lack of knowledge, the objective of this study was to conduct a longitudinal assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Nine of seventeen studies were cross-sectional studies (52.9%). In 2021, Buchanan et al [ 20 ] described the results of teaching first-year students about DV. AlAlyani et al [ 21 ] published a study about the awareness of and actions toward patients who witnessed DV in 2017.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine of seventeen studies were cross-sectional studies (52.9%). In 2021, Buchanan et al [ 20 ] described the results of teaching first-year students about DV. AlAlyani et al [ 21 ] published a study about the awareness of and actions toward patients who witnessed DV in 2017.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study performed in 2021 at the University of Nevada [ 20 ] revealed that a short training for first-year dental students was very successful. A total of 232 participants went through an in-class instructional workshop with integrated pre- and post-testing; 62.5% of the 232 students were male.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations